(untitled) (Maharaja Surajmal Institute Law Journal, 2026)
The paper examines critically the Indian e-rickshaw sector by analyzing the regulatory framework governing it, drawn from key judicial interventions around its registration,licensing, insurance, and safety compliance. It further discusses how contract law applies to daily passenger-driver interactions by setting up implied duties of safety, care, and fairness. Finally, the study also evaluates the innovative Battery as a Service model, being a hybrid contractual approach with impact on the reliability of the vehicle. The central argument isthat the true legitimacy of the e-rickshaw sector relies on the robust inter play between itslegal regulations, contractual relationships, and technological standards. Only through the coordinated strengthening of these elements can e-rickshaws be integrated as a safe, lawful, and sustainable component of India’s urban transport landscape.